A Study on the Work Life Balance of Women in Telecommunication Industry- A Review of LiteratureAnalysing the facts and figures, women generate just 17% of the India’s GDP. From the census of 2011, it is calculated that women labour workforce has declined - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2020)
Analysing the facts and figures, women generate just 17% of the India’s GDP. From the census of 2011, it is calculated that women labour workforce has declined from 35% to 26.6% at present against 53.26% of men. It is seen and proven that agriculture accommodates larger section of the women in comparison to any other sectors, also 13% of the agricultural land is controlled by women. Even after the law has been passed for equal pay to bring equality, women are paid 62% lesser than that of the men. The data for this research paper is collected from the secondary sources. The research paper highlights the life of the women while they work and the way they bring balance to their life. It was found that hindrances from the work and home balance affects the physical and psychological conditions of women and they did not get any ‘me time’ or personal life between that.